Breaking and entering : the extraordinary story of a hacker called "Alien" - Smith, Jeremy N (Houghton Mifflin Harcourt, 2019)
"This taut, true thriller takes a deep dive into a dark world that touches us all, as seen through the brilliant, breakneck career of an extraordinary hacker - a woman known only as Alien"--